2015
DOI: 10.1007/s10967-015-4251-x
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution evaluation of 166Ho–DTPA–SPION in normal rats

Abstract: Super paramagnetic iron oxide nanoparticles (SPION) with a cross-linked dextran coating can be used as a negative contrast agent in magnetic resonance imaging agent. This study describes the preparation, biodistribution of 166 Ho-DTPA-SPIONs after intravenous injection in normal Wistar rats. The biodistribution of 166 Ho-DTPASPIONs showed dramatic uptake in reticuloendothelial system (i.e., more than 60 and 15 % of injected dose was in liver and spleen at 30 min post-injection, respectively) and the clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…PEGylation can improve the uptake in lymph nodes and increase accumulation at the disease site by reducing the nonspecific interaction between particles and proteins of the biological milieu, thus causing a longer blood circulation time . On the other hand, several studies confirmed that Dextran coated NPs resulted in RES uptakes due to the protein corona formation (see the section 4.6) .…”
Section: Resultsmentioning
confidence: 99%
“…PEGylation can improve the uptake in lymph nodes and increase accumulation at the disease site by reducing the nonspecific interaction between particles and proteins of the biological milieu, thus causing a longer blood circulation time . On the other hand, several studies confirmed that Dextran coated NPs resulted in RES uptakes due to the protein corona formation (see the section 4.6) .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reveals that a hydrodynamic size of 85 nm also induces a rapid clearance. 36 Moreover, it has been previously reported that positively charged nanoparticles can lead to nonspecific internalization rate and short blood circulation half-life. 61 Nevertheless, after 48 h, a small activity in blood (1% ID g –1 ) and heart (2% ID g –1 ) is still detected (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few PET/MRI bimodal imaging contrast agents based on iron oxide NPs have been developed. 6,13,21,3136 Patel et al reported a PET/MRI imaging contrast agent using iron oxide NPs coated with DOTA to chelate Cu 2+ . 6 Lee et al developed a tumor-specific iron oxide probe for early clinical tumor detection using PET/MRI multimodal imaging.…”
Section: Introductionmentioning
confidence: 99%
“…A polydentate acyclic chelator, DTPA is commonly used in the construction of MRI and nuclear imaging agents (Brücher, 2002; Frullano & Caravan, 2011; Price & Orvig, 2014). For radiopharmaceuticals, it has been used for labeling with many radiometal ions such as 99m Tc (D. Cheng et al, 2015; H. Gao et al, 2016), 111 In (G. Zhang et al, 2009), 67 Ga/ 68 Ga (de Souza Albernaz et al, 2018; Shanehsazzadeh et al, 2013), and 166 Ho (Nosrati et al, 2016). Given its acyclic nature, DTPA and its derivatives can be readily labeled with metal radionuclides (matter of minutes) (Price & Orvig, 2014).…”
Section: Radiolabeling Of Mnpsmentioning
confidence: 99%